2018
DOI: 10.18203/2394-6040.ijcmph20180259
|View full text |Cite
|
Sign up to set email alerts
|

Quality of marital relationship, partner violence, psychological distress, and resilience in women with primary infertility

Abstract: Background: Primary infertility is an emerging public health problem associated with immense social stigma and adverse mental health consequence. The impact associated with infertility different from culture to culture. There is a paucity of qualitative research in Indian culture. Hence we aimed to explore the quality of marital relationship, psychological distress and resilience in a sample of women with primary infertility.Methods: A cross sectional single group mixed design was used. Sample comprised of 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 22 publications
1
21
1
Order By: Relevance
“…Despite the fact that infertility affects both men and women fairly equally, [7][8][9] in many societies, the woman is most often blamed when she does not get pregnant, resulting in mental health distress, stigma, discrimination, social exclusion, and abandonment. 2,[10][11][12] Infertility is associated with lower quality of life, marital discord, 13 with greater psychosocial consequences for women. 3,14 Additionally, infertile women with poor social support, high sociocultural pressure to have children (especially sons), maladaptive coping (ie, emotion focused/avoidance), prior trauma or mental health disorders, and overinvolved family members, are at particularly high risk for distress, including depression, and anxiety.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite the fact that infertility affects both men and women fairly equally, [7][8][9] in many societies, the woman is most often blamed when she does not get pregnant, resulting in mental health distress, stigma, discrimination, social exclusion, and abandonment. 2,[10][11][12] Infertility is associated with lower quality of life, marital discord, 13 with greater psychosocial consequences for women. 3,14 Additionally, infertile women with poor social support, high sociocultural pressure to have children (especially sons), maladaptive coping (ie, emotion focused/avoidance), prior trauma or mental health disorders, and overinvolved family members, are at particularly high risk for distress, including depression, and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…5,13,15,21,22 Furthermore, in traditional patriarchal societies such as many found in India, a woman's status and value is inextricably linked to her fertility. 5,10,12 Although allopathic infertility treatment and reproductive technology is readily available in India, it is not equally available to all due to the expense and time-intensive nature of treatment. 3,12,23 Sarkar and Gupta 3 found that while roughly 80% of infertile women in India sought treatment, 33% of these treatments were classified as traditional treatments or religious rituals.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations